A NOTE ON A DUAL SCHEME OF A LINEAR FRACTIONAL PROGRAMMING PROBLEM - Son, T. Q.; Khoa, H. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2017)
We are interested in the duality scheme of a linear fractional programming problem proposed by Seshan [11]. The remarkable feature of the duality scheme is that the dual problem and the primal problem have the same linear fractional objective functions. Although the duality scheme is fascinating and has been introduced in literature, the steps how to build the scheme still be silent. The aim of this paper is to show that the dual problem can be obtained based upon the transformation form of Charnes-Cooper or by Dinkelbach with a simple change variable method.